Accumulation potential of Atriplex halimus to zinc and lead combined with NaCl: Effects on physiological parameters and antioxidant enzymes activities - Bankaji, I. (2019)
An experiment in this study was designed to investigate the effect of different concentrations of Zn2+ or Pb2+ (0, 200, 400 and 600 μM) with NaCl (0, 200 mM), on the morphological and physiological parameters as well as the antioxidative response of the halophytic species Atriplex halimus. Results showed that Pb2+ had no significant impact on biomass production while Zn2+ significantly affected plant development mainly at high concentration, 600 μM. Total chlorophyll content did not change significantly under elevation concentrations of Zn2+ when compared to control. However, there was a modest decrease in total chlorophyll concentration in the leaves of A. halimus grown in a medium supplemented with 600 μMPb2+ and with combined stress Pb2+/NaCl. Zn2+ and Pb2+ contents in tissues were higher in the belowground organs of this halophyte. Overall results pointed out that application of different concentrations of Zn2+ or Pb2+ disturbed status of nutrients in A. halimus. Analysis of antioxidant enzymes [ascorbate peroxidase (APX), guaiacol peroxidase (GPX), and catalase (CAT)] showed that the activity was diminished by increasing Zn2+ concentrations in the medium. Whereas, the addition of Pb2+ in the medium increased CAT activity and decreased APX activity.